2016
DOI: 10.1039/c6fo00914j
|View full text |Cite
|
Sign up to set email alerts
|

Mugil cephalus roe oil obtained by supercritical fluid extraction affects the lipid profile and viability in cancer HeLa and B16F10 cells

Abstract: We explored the changes in viability and lipid profile occurring in cancer cells, murine melanoma cells (B16F10 cells) and human cervical carcinoma cells (HeLa cells), when exposed to 24 h-treatments with an n-3 PUFA-rich oil obtained by supercritical extraction with CO2 from Mugil cephalus processed roe (bottarga). The composition of the major lipid classes of bottarga oil was determined by the (13)C NMR technique. Reversed-phase HPLC with DAD/ELSD detection was performed to analyze cells' total fatty acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(89 citation statements)
references
References 47 publications
1
88
0
Order By: Relevance
“…The yeast in flakes was provided from Il Fior di loto Srl (Torino, Italy). Fruits of L. nobilis (Marzouki, Piras, Marongiu, Rosa, & Dessì, ) and P. terebinthus (Piras et al, ), seeds of M. fragrans (Piras et al, ), wheat germ (Piras et al, ), and the salted and semidried mullet ( M. cephalus ) ovary product (bottarga; Rosa et al, ) were obtained as previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The yeast in flakes was provided from Il Fior di loto Srl (Torino, Italy). Fruits of L. nobilis (Marzouki, Piras, Marongiu, Rosa, & Dessì, ) and P. terebinthus (Piras et al, ), seeds of M. fragrans (Piras et al, ), wheat germ (Piras et al, ), and the salted and semidried mullet ( M. cephalus ) ovary product (bottarga; Rosa et al, ) were obtained as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…Total lipids were extracted from insect samples (approximately 90 mg of fresh weight, corresponding to 12–13 insects) and aliquots of yeast (100 mg) used for standard diet by the Folch procedure (Folch, Lees, & Sloane Stanley, ), using a mixture of CHCl 3 :MeOH of 2:1 (Rosa et al, ). After addition of H 2 O, the samples were left in the dark at room temperature for 1 hr, centrifuged for 1 hr at 900 g , and the methanol–H 2 O phase was separated from the CHCl 3 phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations